A Review on Design of Smart Device for UV Radiation Measurement (International Journal of Innovative Research in Computer Science & Technology, 2021)
The sun plays an important role in our  health, and too much sun exposure may cause anything  from sunburns to skin cancer. Human skin cancer has  become a growing health issue. Despite the fact that  individuals are aware of the risks, skin damage caused  by sunshine has risen in recent decades. The public  nowadays relies on weather predictions to learn about  UV radiation. For a certain broad region, the author  offers rough or average predictions. To minimize the  impacts of natural background radiation, this article  provides a technique for calculating UV radiance  utilizing UV sensors that detect the radiation and operate  at a 300 nm wavelength. The sensor provides good  detecting results at low and high UV levels, with  response and regeneration durations of 22 seconds and  39 seconds, respectively. Using a Raspberry Pi and an LCD display, the author may also monitor and see the  preventive steps that need to be performed.
Keywords: LCD Display; Sensor; UV measurement; UV Radiation